Pengaruh Keterampilan Manajerial Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru Sekolah Dasar di Kecamatan Bonang Kabupaten Demak - Noor Miyono; Hasan Taukhid (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This study aims to determine the influence of the principal managerial skills and motivation to work on the performance teachers in the primary school district Bonang Demak. The study population was 189 teachers a public elementary school in District Bonang. The sample consisted of 128 teachers with proportional random sampling technique. Data were collected by questionnaire. The test results showed that the correlation between variables correlation value of managerial skills the principal with teacher performance of 0.878. The correlation between work motivation with teacher performance of 0.863. The regression results show that: (1) the influence of the principal managerial skills on teacher performance amounted to 77.1%, (2) the influence of work motivation on teacher performance amounted to 74.6%, and (3) the influence of the principal managerial skills and motivation together on teacher performance amounted to 87.7% with the regression equation Y = 1,521 + 0.473 X1 + 0,399 X2. From these findings it can be concluded that the fluctuations in the rise and fall of teacher performance is strongly influenced by the dynamics of managerial principals and teachers work motivation.